1998
DOI: 10.1074/jbc.273.35.22589
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Transcript Elongation Factor (TFIIS), Structure and Function

Abstract: TFIIS is a general transcription elongation factor that helps arrested RNA polymerase II elongation complexes resume transcription. We have previously shown that yeast TFIIS (yTFIIS) comprises three structural domains (I-III). The three-dimensional structures of domain II and part of domain III have been previously reported, but neither domain can autonomously stimulate transcription elongation. Here we report the NMR structural analysis of residues 131-309 of yTFIIS which retains full activity and contains al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
39
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 33 publications
(32 reference statements)
2
39
0
Order By: Relevance
“…TFIIS is composed of three domains that fold independently, as demonstrated by NMR analysis of its structure (6,7). Cleavage-stimulating activity minimally requires the Cterminal two-thirds of the protein, that is, its domain II and III separated by a 15-aa linker (7,8).…”
mentioning
confidence: 99%
“…TFIIS is composed of three domains that fold independently, as demonstrated by NMR analysis of its structure (6,7). Cleavage-stimulating activity minimally requires the Cterminal two-thirds of the protein, that is, its domain II and III separated by a 15-aa linker (7,8).…”
mentioning
confidence: 99%
“…The second domain of TFIIS, residues 131-240 in yeast, is ␣-helical (1,2). Deletion analysis as well as site-directed mutagenesis have shown that this region of the protein binds to the polymerase (27,28,30).…”
mentioning
confidence: 99%
“…This region is able to interact with nucleic acids in vitro, although very weakly, and the functional significance of this interaction is not known. Domains II and III are connected with a linker region of about 30 amino acids (2). In yeast TFIIS, this linker region had no defined conformation based on NMR analysis, but also it was not fully flexible (2).…”
mentioning
confidence: 99%
See 2 more Smart Citations